Evaluating associations between patient-to-nurse ratios and mortality, process of care events and vital sign documentation on paediatric wards: a secondary analysis of data from the EPOCH cluster-randomised trial - Orsola Gawronski; Corrado Cecchetti; Emanuela Tiozzo; Marta Luisa Ciofi degli Atti; Massimiliano Raponi; Karen Dryden-Palmer; Christopher S Parshuram; George Tomlinson; Immacolata Dall'Oglio; Leah Szadkowski; Ari Robin Joffe (BMJ Open)
Objective To describe the associations between patient-to-nurse staffing ratios and rates of mortality, process of care events and vital sign documentation.Design Secondary analysis of data from the evaluating processes of care and outcomes of children in hospital (EPOCH) cluster-randomised trial.Setting 22 hospitals caring for children in Canada, Europe and New Zealand.Participants Eligible hospitalised patients were aged>37 weeks and <18 years.Primary and secondary outcome measures The primary outcome was all-cause hospital mortality. Secondary outcomes included five events reflecting the process of care, collected for all EPOCH patients; the frequency of documentation for each of eight vital signs on a random sample of patients; four measures describing nursing perceptions of care.Results A total of 217 714 patient admissions accounting for 849 798 patient days over the course of the study were analysed. The overall mortality rate was 1.65/1000 patient discharges. The median (IQR) number of patients cared for by an individual nurse was 3.0 (2.8–3.6). Univariate Bayesian models estimating the rate ratio (RR) for the patient-to-nurse ratio and the probability that the RR was less than one found that a higher patient-to-nurse ratio was associated with fewer clinical deterioration events (RR=0.88, 95% credible interval (CrI) 0.77–1.03; P (RR<1)=95%) and late intensive care unit admissions (RR=0.76, 95% CrI 0.53–1.06; P (RR<1)=95%). In adjusted models, a higher patient-to-nurse ratio was associated with lower hospital mortality (OR=0.77, 95% CrI=0.57–1.00; P (OR<1)=98%). Nurses from hospitals with a higher patient-to-nurse ratio had lower ratings for their ability to influence care and reduced documentation of most individual vital signs and of the complete set of vital signs.Conclusions The data from this study challenge the assumption that lower patient-to-nurse ratios will improve the safety of paediatric care in contexts where ratios are low. The mechanism of these effects warrants further evaluation including factors, such as nursing skill mix, experience, education, work environment and physician staffing ratios.Trial registration number EPOCH clinical trial registered on clinical trial.gov NCT01260831; post-results.